Clinical outcomes in sensitized heart transplant patients bridged with ventricular assist devices. (30th April 2015) - Kidambi, Sumanth; Mohamedali, Burhan; Bhat, Geetha
Abstract Background Left ventricular assist devices (LVADs) as a bridge to transplant (BTT) have been known to cause allosensitization, as measured by panel‐reactive antibody (PRA) levels. The goal of this study was to measure the impact of this allosensitization on outcomes. Methods Panel‐reactive antibodies were analyzed in BTT patients, with sensitization defined as peak PRAs ≥ 10%. Baseline characteristics and outcomes in the two patient groups were evaluated using descriptive statistics, Kaplan–Meier, and regression analysis. Results Thirty‐eight patients were included in the study (17 sensitized vs. 21 non‐sensitized). There were more women in the sensitized group (47% vs. 10%, p = 0.023). There was no difference in mean times to high‐grade acute cellular rejection (ACR; 18.3 months in sensitized vs. 36.9 months in non‐sensitized). Five patients in the sensitized groups developed antibody‐mediated rejection (AMR) vs. 0 in the non‐sensitized, and all five patients died (Kaplan–Meier log‐rank p = 0.024). There was also a significant difference in the incidence of infection at the one‐ to six‐month stage (52.9% vs. 19.0%, p = 0.03). Conclusion Sensitization appears to have a negative effect on mortality. This mortality appears to be concentrated in patients with AMR, and we postulate that the development of AMR in a sensitized patient may be a predictor of mortality.